2014
DOI: 10.1371/journal.pone.0087886
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Dopamine Synthesis Capacity and Cell-Level Structure in Human Striatum: A Multi-Modal Study with Positron Emission Tomography and Diffusion Tensor Imaging

Abstract: Positron emission tomography (PET) study has shown that dopamine synthesis capacity varied among healthy individuals. This interindividual difference might be due to a difference in the cell-level structure of presynaptic dopaminergic neurons, i.e., cellular density and/or number. In this study, the relations between the dopamine synthesis capacity measured by PET and the parameter estimates in diffusion tensor imaging (DTI) in striatal subregions were investigated in healthy human subjects. DTI and PET studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…MD seems to be useful in detecting specific relationships between myelin loss, axonal damage, and diffusivity (Winston 2012 ). Assuming that MD reflects the density of widespread axonal terminals in the striatum, dopamine synthesis may be related to the density of dopaminergic neuronal fibres (Kawaguchi et al 2014 ). Dopaminergic function in the basal ganglia is thought to be a key regulator contributing to behavioural adaptation (Nieoullon and Coquerel 2003 ; Schiffer et al 2015 ), because the firing of dopamine neurons may provide a learning signal that guides future behaviours by modulating motivation and altering one’s willingness to initiate behaviour and expend effort (Hamid et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD seems to be useful in detecting specific relationships between myelin loss, axonal damage, and diffusivity (Winston 2012 ). Assuming that MD reflects the density of widespread axonal terminals in the striatum, dopamine synthesis may be related to the density of dopaminergic neuronal fibres (Kawaguchi et al 2014 ). Dopaminergic function in the basal ganglia is thought to be a key regulator contributing to behavioural adaptation (Nieoullon and Coquerel 2003 ; Schiffer et al 2015 ), because the firing of dopamine neurons may provide a learning signal that guides future behaviours by modulating motivation and altering one’s willingness to initiate behaviour and expend effort (Hamid et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As explained in a previous study from our research group (Nakagawa et al 2016 ), a decreased MD value, which represents decreased water diffusivity on an MRI scan, is related to increased tortuosity and a decreased volume fraction of the fast diffusivity extracellular compartment. Positron emission tomography (PET) studies have revealed that the capacity for dopamine synthesis is negatively related to MD in the posterior caudate and putamen (Kawaguchi et al 2014 ). Interestingly, the right caudate and putamen of mice exposed to a psychostimulant (methamphetamine) exhibited an increase in MD with no changes in FA compared with mice exposed to saline (McKenna et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the combination of MD, FA and R2* (inverse of relaxation times, i.e., relaxation rates values) in the dopaminergic system has been shown to be the best discriminator between patients with Parkinson’s disease and healthy controls 24 . There was a significant negative correlation between dopamine synthesis capacity and MD in the posterior caudate and putamen using MD with positron emission tomography (PET) 40 . Assuming that MD reflects the density of widespread axonal terminals in the striatum, dopamine synthesis may be related to the density of dopaminergic neuronal fibres 40 .…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant negative correlation between dopamine synthesis capacity and MD in the posterior caudate and putamen using MD with positron emission tomography (PET) 40 . Assuming that MD reflects the density of widespread axonal terminals in the striatum, dopamine synthesis may be related to the density of dopaminergic neuronal fibres 40 . Hence, MD could detect neural plasticity, especially in the dopaminergic system.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to creativity or creative potential, recent neuroimaging studies have shown an association between CPMDT and dopamine receptor binding potential (De Manzano et al, 2010 ). Furthermore, mean diffusivity (MD) in the areas of the dopaminergic system, which is associated with dopamine synthesis capacity (Kawaguchi et al, 2014 ), displays an association with CPMDT (Takeuchi et al, 2015 ). These findings are congruent with the theory based on a wide range of evidence stating that the dopaminergic neural system may facilitate creativity through motivation as well as other dopamine-dependent cognitive processes, such as goal-directed thoughts and seeking behaviors (Flaherty, 2005 ).…”
Section: Introductionmentioning
confidence: 99%